Product Test of PostureCare as a Transformation of Kyphosis Posture Therapy Intervention in Children Integrated with The Internet of Things - Hardiansyah, Farid; Anwar, Mochamad Saiful; Afif, Refaldi Ananta; Angelica, Stephania; Aditya, Irfan; Nurussa'adah, Nurussa'adah; Fatma, Endah Panca Lydia (Department of Nursing, Faculty of Health Sciencce, Universitas Brawijaya, 2025)
Spinal disorders have been observed to increase during the COVID-19 pandemic. The prevalence of prolonged sitting habits during this period has significantly contributed to the rise in spinal disorders. According to the World Health Organization (WHO), between 250,000 and 500,000 individuals worldwide experience spinal disorders annually. Kyphosis, specifically, is frequently identified in children aged 7 to 11 years. In adolescents, kyphosis may be effectively managed through brace therapy. Although various braces are available in the market, they do possess certain limitations. To address such limitations, a technology named PostureCare has been developed to monitor spinal alignment during brace therapy. This technology enables the plotting of graphs enhanced by Internet of Things (IoT) connectivity within an application, thereby facilitating easier data monitoring for users and caregivers. The objective of this research is to design, test, and further develop the PostureCare application. The methodologies employed in this study encompass a literature review, the design and creation of tools and applications, followed by rigorous testing and evaluation. Testing of PostureCare was conducted on two children, during which gyroscopic sensor data were compared to readings from an inclinometer. The results indicated a cervical sensor deviation of 0.85° and a lumbar sensor deviation of 0.791°. The temperature assessment of the heating element revealed a range between 36°C and 40°C. Additionally, the vibration module was activated when the cervical sensor detected a tilt exceeding 25 degrees. Testing results from both children over a seven-day period demonstrated that the cervical sensor recorded an angle of less than 16°, with no signs indicating the presence of kyphosis. It can be concluded that PostureCare has been validated as a tool for detecting spinal ergonomics that may contribute to the development of kyphosis.